Toward Peaceful Coexistence: Islamic Teachings’s Contribution to Christian-Muslim Conflict Reconciliation in Nigeria - Favour C. Uroko; Khairul Amin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Nigeria is characterized by significant religious diversity, especially between Islam and Christianity, which has historically led to frequent horizontal conflicts influenced by religious, social, political, and economic factors. The tensions have been further exacerbated by religious conversion disputes, the enforcement of Sharia law in several northern states, socioeconomic disparities, and the rise of extremist organizations such as Boko Haram. This essay seeks to analyze the influence of Islamic teachings in promoting harmonious coexistence and explores the participation of Muslim youth in addressing Muslim–Christian disputes in Nigeria. This study utilizes a qualitative, library-based research methodology, drawing on primary Islamic texts (the Qur’an and Hadith), relevant scholarly literature, and documented of religious conflict and peacebuilding in Nigeria. The results demonstrate that Islamic teachings significantly prioritize justice, tolerance, compassion, discussion, and forgiveness as essential tenets for harmonious coexistence within religiously diverse communities. These ethical norms are both normative and provide practical guidelines for conflict resolution. Moreover, the study highlights the crucial role of Muslim youth in Nigeria as agents of peace through their involvement in interfaith discussion, community-based projects, peace education, and grassroots organizations that involve young individuals from diverse religious backgrounds. Their active involvement fosters the restoration of trust, diminishes bias, and interrupts cycles of violence among religious communities. This study suggests that the incorporation of Islamic ethical values and the proactive involvement of Muslim youth significantly contribute to sustained reconciliation and harmonious cohabitation between Muslims and Christians in Nigeria. Nigeria merupakan negara dengan keragaman agama yang tinggi, terutama Islam dan Kristen, yang dalam sejarahnya kerap mengalami konflik horizontal bernuansa keagamaan, sosial, politik, dan ekonomi. Ketegangan tersebut diperparah oleh isu konversi agama, penerapan hukum syariah di beberapa negara bagian Nigeria Utara, ketimpangan pembangunan, serta munculnya kelompok ekstremis seperti Boko Haram. Artikel ini bertujuan untuk menganalisis peran ajaran Islam tentang koeksistensi damai serta keterlibatan generasi muda Muslim dalam upaya rekonsiliasi konflik antara Muslim dan Kristen di Nigeria. Penelitian ini menggunakan metode studi pustaka dengan mengkaji sumber-sumber primer Islam (al-Qur’an dan hadis), literatur akademik, serta laporan dan dokumen terkait konflik dan perdamaian di Nigeria. Hasil kajian menunjukkan bahwa ajaran Islam secara normatif menekankan nilai keadilan, toleransi, kasih sayang, dialog, dan pemaafan sebagai fondasi koeksistensi damai dalam masyarakat plural. Nilai-nilai ini tidak hanya relevan secara teologis, tetapi juga memiliki implikasi praktis dalam proses rekonsiliasi konflik. Selain itu, generasi muda Muslim di Nigeria memainkan peran strategis sebagai agen perdamaian melalui dialog lintas agama, kegiatan sosial bersama, pendidikan perdamaian, dan gerakan akar rumput yang melibatkan pemuda lintas iman. Keterlibatan aktif generasi muda ini memperkuat upaya rekonsiliasi dengan membangun kepercayaan, mengurangi prasangka, serta memutus siklus kekerasan antar komunitas. Dengan demikian, integrasi ajaran Islam tentang koeksistensi damai dan partisipasi generasi muda Muslim memiliki kontribusi signifikan dalam membangun perdamaian berkelanjutan antara Muslim dan Kristen di Nigeria.